KONSEP PENDIDIKAN ETIKA DALAM BERIBADAH (KAJIAN Q.S AL-ISRA AYAT 110) - Deka Igus Saputri; Maryono Maryono; Akhmad Khoiri (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to: 1. (Al Isro:110. 2. Determine the relevance of ethics education in worship. 3. To clarify the background of the concept of ethics education in contemporary worship.